Immunotherapy for Management of Thymic Epithelial Tumors: A Double-Edged Sword - Madison Ballman (Cancers, 2022)
Thymic epithelial tumors (TETs) are rare thoracic cancers that are broadly classified as thymomas and thymic carcinomas. Surgery is the cornerstone of management for early-stage disease. There are a limited number of effective treatment options for patients with advanced or recurrent disease. The occurrence of paraneoplastic autoimmune disorders in patients with TETs, especially thymomas, creates significant challenges for the development of immunotherapy, including immune checkpoint inhibitors, as a feasible treatment option. In addition, patients with TETs are at increased risk for the development of immune-mediated toxicity with a predilection for musculoskeletal and neuromuscular adverse events upon treatment with immunotherapy. The identification of biomarkers of response and toxicity is expected to play a key role in harnessing the benefits of immunotherapy for patients with TETs. In this paper we review the biology of TETs and the potential effects on the tolerability of immunotherapy. The results of clinical trials of immune checkpoint inhibitors for the treatment of advanced TETs are described to understand the potential risks and benefits of immunotherapy. We also provide an overview of future avenues for treatment with novel immunotherapeutic modalities and opportunities to develop biomarkers to improve the safety and tolerability of immunomodulatory treatments in patients with TETs.